The Effect of Exchange Rate on Export in Nigeria: An Econometric Analysis - Abdullahi Sule, Sani; Hakim, Lukman; Rahayu, Siti Aisyah Tri; Samudro, Bhimo Rizky; Putro, Tetuko Rawidyo; Pamungkas, Putra (Eastasouth Institute, 2023)
The study's objectives are to assess other important factors that influence export promotion and explore the impact of exchange rates on export performance. To accomplish the research goals, the study uses both the theories of foreign exchange and international trade. Data from the CBN Bulletin from 2010 to 2021 were used in the analysis. Multiple regression analysis was used to analyze the study. The results show that the link between the exchange rate, FDI, and export value in Nigeria is both positive and insignificant. The outcome further demonstrates that FDI and export value in Nigeria have a favorable and significant relationship. This suggests that export encouragement increases with FDI levels. The findings indicate that Nigeria's export performance is negatively and insignificantly correlated with inflation. More specific policies should be implemented by the government to support export promotion in Nigeria.